(untitled) (Fiep Bulletin - online, 2013)
The physical activity is an important factor in the prevention and treatment of the osteoporosis. The aging, relentless process to the alive beings, leads to a progressive loss of the bone mineral density (DMO) of the organism, increasing the risk of falls and fractures. The maintenance of DMO is very important for the prevention of the osteoporosis. The practice of physical exercise, besides combatting the sedentarismo, contributed in a significant way to the maintenance of the senior’s DMO. Some educational programs have been appearing in the sense of to guide the participants in relation to the level of physical activity for prevention and to aid them in the treatment of the osteoporosis, what is not almost always included in the public health politics. Although they are already very established the benefits of the changes in the life habits as an important soft factor related to the bone health, his/her importance, the improvement of the quality of life and the knowledge that the prevention of loss of bone mass can be made with the regular practice of physical exercise not always it is of the knowledge of the population. In this study it was aimed at to determine the changes in relation to adhesion the physical activity in participant women of prevention programs and osteoporosis treatment in hospital public exercises. They participated in the study 173 women registered in the Program of Osteoporosis of public hospital of Fortaleza-CE, above 65 years that answered 2 forms. A program of physical activities was offered to evaluate the level of the studied women’s adhesion. The results presented a low adhesion due to the distance of the residence place. The patients presented interest in practice of exercises once, all that submitted to the evaluation did her with interest in the program of exercises. Is Important the creation of public politics that offer programs of exercises of easy access and that you/they contain well evaluations physical sitemáticas besides a training dimensionado in volume and intensity.